2020
DOI: 10.1136/jitc-2020-001240
|View full text |Cite
|
Sign up to set email alerts
|

Camrelizumab plus gemcitabine and oxaliplatin (GEMOX) in patients with advanced biliary tract cancer: a single-arm, open-label, phase II trial

Abstract: BackgroundImmune checkpoint inhibitors monotherapy has been studied in patients with advanced biliary tract cancer (BTC). The aim of this study was to assess the efficacy and safety of camrelizumab, plus gemcitabine and oxaliplatin (GEMOX) as first-line treatment in advanced BTC and explored the potential biomarkers associated with response.MethodsIn this single-arm, open-label, phase II study, we enrolled stage IV BTC patients. Participants received camrelizumab (3 mg/kg) plus gemcitabine (800 mg/m2) and oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
101
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 25 publications
14
101
2
1
Order By: Relevance
“…A recent study in advanced refractory BTC patients treated with nivolumab demonstrated that lower levels of PD-L1 in tumors were associated with reduced PFS, but not with lower OS [ 96 ]. A similar result was observed in advanced BTC patients treated with camrelizumab plus GEMOX as a first-line treatment since the ORR was worse in patients with lower PD-L1 levels in tumors than in those with higher levels [ 100 ]. However, in two clinical trials, including patients with advanced biliary cancer, most of them refractory to other therapies, no correlation between PD-L1 levels and response to pembrolizumab monotherapy was found [ 97 ]).…”
Section: Immunotherapysupporting
confidence: 69%
See 2 more Smart Citations
“…A recent study in advanced refractory BTC patients treated with nivolumab demonstrated that lower levels of PD-L1 in tumors were associated with reduced PFS, but not with lower OS [ 96 ]. A similar result was observed in advanced BTC patients treated with camrelizumab plus GEMOX as a first-line treatment since the ORR was worse in patients with lower PD-L1 levels in tumors than in those with higher levels [ 100 ]. However, in two clinical trials, including patients with advanced biliary cancer, most of them refractory to other therapies, no correlation between PD-L1 levels and response to pembrolizumab monotherapy was found [ 97 ]).…”
Section: Immunotherapysupporting
confidence: 69%
“…In another study with PD-L1-positive gemcitabine/cisplatin-refractory BTC patients, a durable efficacy of pembrolizumab with an ORR of 9.8% was found [ 99 ]. Camrelizumab, another PD-1 inhibitor, combined with chemotherapy as first-line treatment of BTCs, showed promising results with 50% ORR and a median OS of 11.8 months [ 100 ]. The combination of pembrolizumab and ramucirumab, an antibody that targets VEGFR-2, also seemed to be beneficial as a second-line treatment for patients with advanced BTC, showing a reduction of tumor size of 37.5% and a DCR of 38.5% [ 101 ].…”
Section: Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapy combined with chemotherapy (camrelizumab plus GEMOX [a gemcitabine and oxaliplatin regimen]) has been investigated and shown promising antitumor efficacy in biliary tract cancer. 45 Research focused on reported results for specific biliary tract subsites and high-risk patient subgroups is another avenue for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Pembrolizumab provides durable antitumor activity in 6-13% of patients with advanced biliary tract cancer regardless of programmed cell death 1 ligand 1 (PD-L1) expression and has manageable toxicity. Other immune checkpoint inhibitors were also evaluated in phase I or II studies involving both naïve and refractory advanced biliary tract cancer [74][75][76][77][78][79]. The results of these studies were promising, and further large-scale evaluation is underway.…”
Section: Second-line Chemotherapy For Advanced Biliary Tract Cancermentioning
confidence: 99%